ANALISIS PERSEPSI PETANI DALAM PENGGUNAAN PESTISIDA KIMIA TERHADAP EKOSISTEM SAWAH DI KABUPATEN JEMBER - Ega Bonansyah Utoyo; Sudarti Sudarti (AGRORADIX : Jurnal Ilmu Pertanian, 2022)
Agriculture has been an activity practiced by humans since ancient times. In the process of raising many pests that attack plants, farmers have resorted to pesticides especially chemical pesticides to ward off pests. Studies are therefore used to analyze the farmers' perceptions in the use of chemical pesticides to rice field ecosystems. The study uses a descriptive quantitative study to explain the farmers' perceptions of the use of chemical pesticides to rice ecosystems by using a method of direct interviews to farmers by using the questionnaires provided by the ajung district responders. Research data analysis using data interpretation analysis of the farmer's perceptions in the use of chemical pesticides to rice field ecosystems. Studies have shown that farmers use chemical pesticides more often than organic pesticides and that the majority of farmers have a perception that chemical pesticides will not affect rice field ecosystems. From the results of data and analysis, one might conclude that the farmers' perceptions level of the use of chemical pesticides to rice field ecosystems is still low.